Rehabilitation clinicians' perspectives of reactive balance training. Issue 25 (4th December 2022) - Jagroop, David; Houvardas, Stephanie; Danells, Cynthia J.; Kochanowski, Jennifer; French, Esmé; Salbach, Nancy M.; Musselman, Kristin; Inness, Elizabeth L.; Mansfield, Avril
Abstract: Purpose: Reactive balance training (RBT) aims to improve reactive balance control. However, because RBT involves clients losing balance, clinicians may view that it is unsafe or not feasible for some clients. We aimed to explore how clinicians implement RBT to treat balance and mobility issues. Materials and methods: Physiotherapists and kinesiologists across Canada who reported that they include RBT in their practices were invited to complete telephone interviews about their experiences with RBT. Interviews were transcribed verbatim, and analysed using a deductive thematic analysis. Results: Ten participants completed telephone interviews, which lasted between 30-60 min. Participants primarily worked in a hospital setting (inpatient rehabilitation ( n  = 3); outpatient rehabilitation ( n  = 2)), and were treated clients with neurological conditions ( n  = 5). Four main themes were identified: 1) there is variability in RBT approaches; 2) knowledge can be a barrier and facilitator to RBT; 3) reactive balance control is viewed as an advanced skill; and 4) RBT experience builds confidence. Conclusions: Our findings suggest a need for resources to make clinical implementation of RBT more feasible. Implications for rehabilitation: Trust between the therapist and client improves self-efficacy and feelings of apprehension/fear when conducting reactive balance training. Being creative and improvising with equipment that is readily available in clinics enables reactive balance training, without the need for high-tech equipment. Clinicians should consider using standardized tools with reactive balance control components, such as the Balance Evaluation Systems Test or Performance Oriented Mobility Assessment, to assess balance control.